2021
DOI: 10.1007/s10577-021-09658-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping of histone modifications during axenic growth in two species of Leptosphaeria maculans showing contrasting genomic organization

Abstract: Leptosphaeria maculans ‘brassicae’ (Lmb) and Leptosphaeria maculans ‘lepidii’ (Lml) are closely related phytopathogenic species that exhibit a large macrosynteny but contrasting genome structure. Lmb has more than 30% of repeats clustered in large repeat-rich regions, while the Lml genome has only a small amount of evenly distributed repeats. Repeat-rich regions of Lmb are enriched in effector genes, expressed during plant infection. The distinct genome structures of Lmb and Lml provide an excellent model for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 87 publications
5
16
0
Order By: Relevance
“…The global fraction of genes that are located in H3K27me3 domains in V. dahliae is similar to what has been reported for the ascomycete Podospora anserina ( 28 ) but higher than those for N. crassa , Zymoseptoria tritici , Leptosphaeria maculans , and Magnaporthe oryzae (9 to 16% of genes in H3K27me3 domains) ( 20 , 30 , 32 , 50 ). Previous reports showed that H3K27me3 represses the transcription of secondary metabolite clusters in Fusarium spp.…”
Section: Discussionsupporting
confidence: 82%
“…The global fraction of genes that are located in H3K27me3 domains in V. dahliae is similar to what has been reported for the ascomycete Podospora anserina ( 28 ) but higher than those for N. crassa , Zymoseptoria tritici , Leptosphaeria maculans , and Magnaporthe oryzae (9 to 16% of genes in H3K27me3 domains) ( 20 , 30 , 32 , 50 ). Previous reports showed that H3K27me3 represses the transcription of secondary metabolite clusters in Fusarium spp.…”
Section: Discussionsupporting
confidence: 82%
“…As noticed when having cloned the first avirulence gene of L. maculans more than a decade ago (Gout et al, 2006 ), all of them are “lost in the middle of nowhere” genes isolated in large AT‐rich blocks of degenerated transposable elements (for a review, see Rouxel & Balesdent, 2017 ). In relation to this genome location we also found recently that all AvrLm genes are enriched in H3K9me3 (trimethylation of lysine 9 of histone H3) marks, usually regarded as characteristic of constitutive heterochromatin in other organisms (Soyer et al, 2021 ). Being associated with this repressive mark, none of the AvrLm genes are expressed during vegetative growth (Soyer et al, 2021 ), but all of them show the same kinetics of expression when the fungus is inoculated onto cotyledons of B. napus , with a strong peak of overexpression 5–9 days postinoculation before symptoms are expressed (Figure 3 ) (Gay et al, 2021 ).…”
Section: Discussionsupporting
confidence: 70%
“…In relation to this genome location we also found recently that all AvrLm genes are enriched in H3K9me3 (trimethylation of lysine 9 of histone H3) marks, usually regarded as characteristic of constitutive heterochromatin in other organisms (Soyer et al, 2021 ). Being associated with this repressive mark, none of the AvrLm genes are expressed during vegetative growth (Soyer et al, 2021 ), but all of them show the same kinetics of expression when the fungus is inoculated onto cotyledons of B. napus , with a strong peak of overexpression 5–9 days postinoculation before symptoms are expressed (Figure 3 ) (Gay et al, 2021 ). Additionally, all of them encode small secreted proteins, often but not always enriched in cysteine residues, and showing no or few matches in databases, no recognizable domain, and no postulated function.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Recognition by the host activates the host immune response, including the deployment of antimicrobial compounds, pH change, and programmed cell death at the infection site [23][24][25]. To successfully hijack host cells, effector expression is orchestrated by alterations in the chromatin state leading to waves of expression changes [26][27][28]. In concert with effector expression, TEs are derepressed during the early infection phase [7] (Figure 1A), thus weakening the genome's control of TEs.…”
Section: The Tangled Relationship Between Tes and Pathogen Virulencementioning
confidence: 99%